Characterization of underwater shock transient effects on naval E-glass biaxial fiberglass laminates: An experimental and numerical method. (November 2022) - Mannacio, F.; Di Marzo, F.; Gaiotti, M.; Guzzo, M.; Rizzo, C.M.; Venturini, M.
Highlights: Underwater explosions can cause large deformations on naval composite structures. Historically transient effects on fiberglass are predicted by quasi-static methods. A dedicated shock test campaign is realized to characterize laminates dynamically. A dynamic finite element model is validated to predict shock response in tests. Experimental+numerical analyses validate modeling strategies for ships shock design. Abstract: Non-contact underwater explosions (UNDEX) can cause extremely large deformations on naval composite structures related to heavily nonlinear phenomena. For this reason, for military purposes, used materials must have excellent shock resistance properties. Historically, the underwater shock transient effects on fiberglass laminates are predicted using quasi-static approaches. In this paper, the composite materials are characterized by experimental modal analysis as well as by a comprehensive series of shock tests, whose results are compared with numerical models. Namely, the MIL S 901 D Medium Weight Shock Machine (MWSM) was used to perform dedicated shock tests, in which composite specimens are supported on a special constraining structure designed to create large deflections and providing reproducible results. A dynamic implicit finite element model has been set, validated by modal analysis at first, and then applied to simulate the MWSM test behavior and to predict the structural response of different E-Glass polyester resin laminates. In the end, the complete comparison of numerical results and experimental data is reviewed to validate the modeling strategies for shock design of navy ships.